Minangkabau local wisdom in coastal environmental conservation: An ecocritical review of Wisran Hadi’s drama script Nilonali - Rafdisyam; Agustina; Hayati, Yenni (Research Journal in Advanced Humanities, 2026)
Environmental degradation, particularly in coastal areas, has emerged as a critical challenge facing contemporary society. Addressing this issue requires a comprehensive approach, including the revitalization of local wisdom. This study examined the representation of Minangkabau local wisdom in coastal environmental conservation as portrayed in Nilonali, a drama script by Wisran Hadi, through the lens of ecocriticism. The research identified and analyzed forms of indigenous knowledge, belief systems, and cultural practices contributing to coastal ecological sustainability. Employing qualitative analysis, the study revealed three interrelated categories of local wisdom: (1) local knowledge, encompassing environmentally friendly fishing methods and an understanding of coastal climatology and geophysics; (2) local belief systems, including religious and superstitious values that function as social controls; and (3) cultural practices, particularly the tradition of berpantun (reciting traditional rhymed quatrains), whose lyrical content is inspired by the coastal environment. The findings highlight the ecological significance of Minangkabau local wisdom in fostering environmental protection and ecological awareness among coastal communities.